Antivenom Cross-Neutralization of the Venoms of Hydrophis schistosus and Hydrophis curtus, Two Common Sea Snakes in Malaysian Waters - Choo, Hock Tan; Nget, Hong Tan; Kae, Yi Tan; Kok, Onn Kwong (MDPI, 2015)
Sea snake envenomation is a serious occupational hazard in tropical waters. In Malaysia, the beaked sea snake (Hydrophis schistosus, formerly known as Enhydrina schistosa) and the spine-bellied sea snake (Hydrophis curtus, formerly known as Lapemis curtus or Lapemis hardwickii) are two commonly encountered species. Australian CSL sea snake antivenom is the definitive treatment for sea snake envenomation; it is unfortunately extremely costly locally and is not widely available or adequately stocked in local hospitals. This study investigated the cross-neutralizing potential of three regionally produced anti-cobra antivenoms against the venoms of Malaysian H. schistosus and H. curtus. All three antivenoms conferred paraspecific protection from sea snake venom lethality in mice, with potency increasing in the following order: Taiwan bivalent antivenom < Thai monocled cobra monovalent antivenom < Thai neuro polyvalent antivenom (NPAV). NPAV demonstrated cross-neutralizing potencies of 0.4 mg/vial for H. schistosus venom and 0.8 mg/vial for H. curtus, which translates to a dose of less than 20 vials of NPAV to neutralize an average amount of sea snake venom per bite (inferred from venom milking). The cross-neutralization activity was supported by ELISA cross-reactivity between NPAV and the venoms of H. schistosus (58.4%) and H. curtus (70.4%). These findings revealed the potential of NPAV as a second-line treatment for sea snake envenomation in the region. Further profiling of the cross-neutralization activity should address the antivenomic basis using purified toxin-based assays.